Does the Covid-19 pandemic affect ankle fracture incidence? Moderate decrease in Sweden - Rydberg, Emilia Möller; Möller, Michael; Ekelund, Jan; Wolf, Olof; Wennergren, David (Acta Orthopaedica, 2021)
Background and purpose — While many other countries implemented strict regulations and restrictions for their citizens during the 1st wave of the Covid-19 pandemic, Sweden maintained a more restrained approach. The Swedish Public Health Agency emphasized individual responsibility and pushed for behavioral changes. With strict lockdown a 77% decrease in ankle fracture incidence has been reported. We investigated whether there was a change in the incidence of ankle fractures seen at 7 selected hospitals during the Covid19 pandemic 2020. Patients and methods — Data on all ankle fractures treated at 7 selected departments during March 15 through June 15, 2020, and for the same period in the preceding 3 years (2017–2019), was retrieved from the Swedish Fracture Register. The number of fractures during the whole period and subsequent 30-day periods were compared between 2020 and 2017–2019, including subgroup analyses of age and sex. Results — The monthly rate of ankle fractures was reduced by 14% in 2020 (139 fractures) compared with 2017–2019 (161 fractures). Women had a 16% decrease and patients aged > 70 years had a 29% decrease. During the 1st 30-day period, a 26% decrease in fractures was seen. Interpretation — During the 1st wave of the Covid-19 pandemic, a moderate decline in the number of ankle fractures was seen. Women and patients aged > 70 years displayed the greatest reduction. The greatest reduction in incidence of fractures was seen during the 1st 30-day period. This indicates greater adherence to government recommendations regarding social distancing in these subgroups and during the 1st month of the pandemic. Changes in ankle fracture incidence may be a measure of lockdown extent.